Pelatihan Sablon Dalam Upaya Meningkatkan Sumber Daya Manusia Yang Kreatif Dan Inovatif Dalam Berwirausaha Desa Sunggu Manai Sulawesi Selatan - Ismail, Ismail; Tajuddin, Imran; Fara Kessi, Andi Muhammad (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Sunggu Manai Village is a village located in Pattallasang District, Gowa Regency with an area of 684 ha which has 3 hamlets namely Sailong, Lamuru and Japing Hamlets. The population of Sunggu Manai Village reaches 2,860 people. One of the main and important investments for business actors is human resources which is the key to the success and progress of a business in order to survive and develop properly. Human resources (HR) is a very important factor that cannot even be separated from an organization, both institutions and companies. HR is also the key that determines the development of the company. In order to increase creative and innovative human resources, one of the constructive trainings is conducted, namely screen printing training. In participating in the training, the HR participating in this training must have the motivation to take part in this activity because of course there are business opportunities from this training. However, deficiencies still have to be corrected after attending the initial stage of training, namely with subsequent training and reading various literature in order to perfect optimal work results. Before starting the training, HR who take part in the training are required to make observations first, so that the material presented by the teacher is only seen as increasing knowledge from screen printing training